The second chance club: hardship and hope after prison - Hardy, Jason Matthew (Simon & Schuster)
"A former parole officer shines a bright light on a huge yet hidden part of our justice system through the intertwining stories of seven parolees striving to survive the chaos that awaits them after prison in this illuminating and dramatic book"--